A case of fulminant myocarditis treated with very long-term support by cardiopulmonary support system - Mito, Takahiro (J Cardiol Cases, 2016)
Fulminant myocarditis (FM) sometimes causes severe left ventricular dysfunction and lethal arrhythmias leading to cardiogenic shock and critical conditions. Thus, mechanical circulation support with intra-aortic balloon pumping and/or a cardiopulmonary support system (CPS) is sometimes needed to save lives. The special recommended therapies for FM for that classified as class I (evidence level C) in the guidelines of the Japanese Circulation Society are intra-aortic balloon pumping, CPS, percutaneous cardiac pacing, and a left ventricular assist device (LVAD), and they are well established in evidence-based medicine. We experienced a case of FM that we were able to save by long-term stable CPS support. Because, unfortunately, the LVAD was not commercially available in Japan at that time, intensive treatments including CPS were continued in our hospital. Finally, a good course of the illness was achieved without any adverse complications. Thus, these intensive treatments in the present case may be one of the optional effective strategies for FM, especially in hospitals and/or countries where the LVAD is not (commercially) available, and when an LVAD may not be suitable because of complications associated with infectious disease. <Learning objective: Intensive treatment including cardiopulmonary support system as in this case may be one of the optional effective strategies for fulminant myocarditis, especially in hospitals and/or countries where left ventricular assist devices (LVAD) are not (commercially) available, and when an LVAD may not be suitable because of complications associated with infectious disease.>